Ultrafast Ferroelectric Domain Switching Induced by Nano‐Second Strain‐Pulse. Issue 3 (7th December 2021) - Shi, Xiaoming; Wang, Jing; Cheng, Xingwang; Huang, Houbing
Abstract: Ferroelectric materials subjected to ultrafast external stimuli have been demonstrated to exhibit dynamic phenomena with potential applications in the high‐speed operation of ferroelectric data‐storage devices. A modified phase‐field model is developed to investigate the ferroelectric domain evolution for Pb(Zr, Ti)O3 bulk materials under nano‐second strain‐pulse stimuli. In contrast to the ultrafast electric field pulses, where the ferroelectric domain is switched through domain‐wall motion over the entire duration of the pulses, the nano‐second strain‐pulse induces ultrafast domain switching at the beginning of the pulse, after which the domain structure of the material remains stable. A tensile strain pulse (10 ns) with a critical magnitude of 4.4% is demonstrated to completely switch c domain to a domain. In addition, c domain can also be fully switched to a domain through multiple‐step domain reversals under the periodic small magnitude (2.0%) of strain pulses (5 ns). The theoretical insights obtained in this work are expected to provide useful guidance for exploring and manipulating the ultrafast dynamic functionalities of ferroelectric materials. Abstract : Through applying GHz strain pulse, the quantitative and reversible multiple state domain evolution with ultrafast speed can be obtained. Besides, the periodically applied strain pulse can generate domain switching through the integration process. These two features obtained in ferroelectric materials show the potential application to emulate neurons and synapses devices.